Short Communication: Species composition and diversity of vegetation in dryland agricultural landscape - Ida Ardiyaningrum; MARIA THERESIA SRI BUDIASTUTI; KOMARIAH KOMARIAH (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ardiyaningrum I, Budiastuti MTS, Komariah. 2021. Short Communication: Species composition and diversity of vegetation in dryland agricultural landscape. Biodiversitas 22: 65-71. Drylands are a part of the terrestrial ecosystems with a relatively larger area compared to wetlands. Selo has dryland with steep slopes and high rainfall, resulting in relatively high soil erosion. The land use in this sub-district is dominated by plantations and agriculture, with conditions that have not been fully balanced by trees as a means of controlling erosion and supporting vegetation diversity. Therefore, studies on biodiversity are important as an indicator of dryland sustainability, especially in terms of soil and water conservations. This research aimed to study the species composition and diversity of vegetation in the dryland agricultural landscape in Selo Sub-district, Boyolali District, Central Java Province, Indonesia. Vegetation analysis was performed by using the quadratic sampling technique for tree category, pole category, sapling category, and seedling categories. The results indicated that Fabaceae had the highest number of species. Tree species with the highest Importance Value Index were Toona sureni, Artocarpus heterophyllus, and Casuarina junghuhniana, respectively. The Shanon-Wiener Diversity Index showed that the vegetation at tree, pole, and sapling stages had a moderate diversity, and seedling-stage vegetation had a low diversity.